Pendidikan Inklusif dalam Literatur Akademik: Analisis Bibliometrik Berbasis Scopus - Hermina, Ceria; Purwandari, Eny; Japar, Muhammad (Universitas Muhammadiyah Metro, 2025)
Inclusive Education is currently a concern in order to fulfill the rights of children with special needs to learn. This study aims to conduct a bibliometric analysis of research on the theme of Inclusive Education, identify current conditions, trends and other indicators by analyzing articles sourced from Scopus since 2010-2024. This study examines publications per year, keyword trends, Co-author Analysis, countries and organizations. 414 articles were obtained as samples. This study uses Vosviewer software to analyze the data. This study provides an important basis for further researchers to develop more inclusive education policies and practices. Practically, the results of this study emphasize the need for policies that support teacher training, especially in developing countries, to ensure the achievement of educational inclusivity.